2018
DOI: 10.3389/fnmol.2018.00197
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Psychiatric Disease: A Focus on the Glutamate System

Abstract: Alterations in glutamate, the primary excitatory neurotransmitter in the brain, are implicated in several psychiatric diseases. Many of these psychiatric diseases display epidemiological sex differences, with either males or females exhibiting different symptoms or disease prevalence. However, little work has considered the interaction of disrupted glutamatergic transmission and sex on disease states. This review describes the clinical and preclinical evidence for these sex differences with a focus on two cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 166 publications
(193 reference statements)
6
49
0
1
Order By: Relevance
“…To date, very little work has been done on the characterization of sex differences in the neurochemical profile with age, despite age-related neurodegenerative (and other) disorders such as Alzheimer's disease differring in prevalence and symptom presentation between sexes (Wickens, Bangasser, and Briand 2018;Komoroski et al 1999;Mazure and Swendsen 2016). In a longitudinal study of C57BL6 mice, sex differences were identified for many metabolites, including ones in which we also report effects of sex (i.e.…”
Section: Presence Of Sex-specific Effects In Fisher Rat Hippocampusmentioning
confidence: 88%
“…To date, very little work has been done on the characterization of sex differences in the neurochemical profile with age, despite age-related neurodegenerative (and other) disorders such as Alzheimer's disease differring in prevalence and symptom presentation between sexes (Wickens, Bangasser, and Briand 2018;Komoroski et al 1999;Mazure and Swendsen 2016). In a longitudinal study of C57BL6 mice, sex differences were identified for many metabolites, including ones in which we also report effects of sex (i.e.…”
Section: Presence Of Sex-specific Effects In Fisher Rat Hippocampusmentioning
confidence: 88%
“…Only one study to date has analyzed sex differences in ketamine response and found no differences in efficacy or tolerability (38,39). These studies highlight the need for further studies of sex differences in the behavioral, neural, molecular, and genetic phenotypes of major depressive disorder to inform the development of more effective treatment options (40). Pvalb interneurons are noted for their fast-spiking properties at rest, and could also be involved in ketamine-mediated disinhibition (15).…”
Section: Discussionmentioning
confidence: 99%
“…As with GABA receptors, there are two broad families of glutamate receptors: ionotropic and metabotropic. The ionotropic receptor family can be further subdivided into AMPA, NMDA and kainate receptors . Notably, the subunit GluN2B appears to be preferentially located in extrasynaptic NMDA receptors on immature neurones (particularly GABAergic interneurones).…”
Section: Importance Of Balanced Inhibitory and Excitatory Actionmentioning
confidence: 99%
“…Dysfunction of the GABAergic and glutamatergic systems has been implicated in a number of psychiatric disorders including ADHD, anxiety and depression . Magnetic resonance spectroscopy in children aged between 8‐12 years with ADHD identified reduced concentrations of GABA in the brain compared to children without the disorder .…”
Section: Dysregulation Of Gabaergic and Glutamatergic Pathways In Dismentioning
confidence: 99%
See 1 more Smart Citation